2013
DOI: 10.1590/s0100-06832013000600012
|View full text |Cite
|
Sign up to set email alerts
|

Comportamento dos óxidos de ferro da fração argila e do fósforo adsorvido, em diferentes sistemas de colheita de cana-de-açúcar

Abstract: RESUMONa agricultura, a obtenção de maiores produtividades das culturas com base no manejo sustentável do solo tem levado a uma busca gradativa do conhecimento das variáveis envolvidas nos sistemas de produção. Determinar as causas da variabilidade dos atributos passa a ser uma etapa do planejamento estratégico no setor sucroenergético. Este trabalho teve por objetivo estudar a variabilidade espacial dos óxidos de ferro da fração argila e sua relação com atributos físicos e químicos do solo, em diferentes sist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
3
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 42 publications
(43 reference statements)
1
3
0
1
Order By: Relevance
“…The GDE (0.07%) was classified according to Cambardella et al (1994), in which the variable under study showed strong spatial dependence (< 25%), which coincides with the study by Reichert et al (2008), Barbieri et al (2013) and Aquino et al (2014). While Souza et al (2010) observed moderate GDE for SOM at the depth of 0.0-0.2 m and strong GDE at a depth of 0.2-0.4 m. Cambardella et al (1994) still states that when strong spatial dependence occurs, it means that the variable may be more influenced by the intrinsic properties of the soil.…”
Section: Resultssupporting
confidence: 80%
“…The GDE (0.07%) was classified according to Cambardella et al (1994), in which the variable under study showed strong spatial dependence (< 25%), which coincides with the study by Reichert et al (2008), Barbieri et al (2013) and Aquino et al (2014). While Souza et al (2010) observed moderate GDE for SOM at the depth of 0.0-0.2 m and strong GDE at a depth of 0.2-0.4 m. Cambardella et al (1994) still states that when strong spatial dependence occurs, it means that the variable may be more influenced by the intrinsic properties of the soil.…”
Section: Resultssupporting
confidence: 80%
“…As a dynamic element in nature, P is vital in agriculture, where it is a basic fertilizer [8]. The P dynamics depend on soil factors such as pH, salinity [9], high concentrations of toxic elements, interaction with micronutrients [10], runoff, leaching [11], total P concentration, soluble (and, as such, assimilable for the plants) P pool [12], organic matter content, redox potential [13], soil structure and texture (especially the clay content) [14,15], mineralogical composition [12], enzymatic activity, P-solubilizing microorganisms [16,17], and mycorrhizas [18].…”
Section: Introductionmentioning
confidence: 99%
“…Some studies indicate that P sorption is correlated to the clay fraction content of the soil (Barbieri et al, 2013;Oliveira et al, 2014). However, this correlation is substantially influenced by the content and crystallinity of iron oxides [particularly hematite (Hm), goethite (Gt) and maghemite (Mh)] and aluminum hydroxides [particularly gibbsite (Gb)] ( Barrón and Torrent, 1996;Lair et al, 2009;Broggi et al, 2010;Yoon et al, 2014;Bortoluzzi et al, 2015).…”
Section: Introductionmentioning
confidence: 99%